ANALISIS PELAKSANAAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) BPJS KESEHATAN PADA DOKTER KELUARGA DI KABUPATEN PEKALONGAN TAHUN 2016 - Sarmaulina Sitompul; Chriswardani Suryawati; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Chronic Disease Management Program (Prolanis) is a program of The National Health Care Security (BPJS) to manage chronic diseases namely diabetes mellitus and hypertension in patients to prevent complications, improve the quality of life and health insurance financial effectively and efficiently. Based on the evaluations in 2016, BPJS deficits due to claims and capitation's inflammation fees in 2015. Pekalongan is a region in Central Java Province with the number of cases of hypertension ranks first while type 2 diabetes mellitus ranks second around in 2015. The aim of this study was to determine the implementation Prolanis family doctor in Pekalongan. The research method used by the writer is a qualitative method. The data was obtained from a document review and in-depth interviews. The writer analyzes 16 the informants consisting of family doctors, staffs of MPKP BPJS, the head of KLOK and prolanis participants. The data is presented in narrative form and matrix interview. The result showed that only five doctors who own the Prolanis club of the 18 family doctors in Pekalongan. From 7 activities, there are only 4 activities which had been done, that are health counseling, health checks, gymnastics prolanis and drug delivery. This happens because the limited human resources and funds. Moreover, unavailability of drugs frequently happen. The activities management is different because there is no SOP for the prolanis activities and the implementation of monitoring and evaluation is not optimal.